Adsorption removal of crystal violet from aqueous solution using a metal‐organic frameworks material, copper coordination polymer with dithiooxamide. Issue 5 (6th February 2013) - Li, Xiaojuan; Zheng, Lingyan; Huang, Lianzhu; Zheng, Ou; Lin, Zhenyu; Guo, Longhua; Qiu, Bin; Chen, Guonan
Abstract The potential application of copper coordination polymer with dithiooxamide (H2dtoaCu), one of the metal‐organic frameworks (MOFs) in the adsorption removal of crystal violet (CV) from aqueous solution was studied. Batch adsorption experiments were carried out as a function of initial pH, adsorbent concentration, contact time, initial dye concentration and temperature. The adsorption of CV on H2dtoaCu can be best described by the Langmuir isotherm model (R2 > 0.9983) with maximum monolayer adsorption capacity of 165.83, 185.87, and 204.50 mg g−1 at 298, 308, and 318 K, respectively. The kinetics of CV adsorption followed pseudo‐second‐order model (R2 > 0.9984) and the chemisorption was proved to be rate‐limiting step. Thermodynamic parameters, the change of free energy (ΔG°), entropy (ΔS°) and enthalpy (ΔH°), showed that the adsorption of CV on H2dtoaCu was feasible, spontaneous and endothermic process. Here we concluded that H2dtoaCu is a promising adsorbent for the removal of harmful dyes from aqueous solution. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013